Use and perceptions of the University of the Philippines College of Pharmacy students and faculty on social networking sites, online learning tools and University virtual learning environment - Abergas, Anna Dominique; Elio, Angela Estrella; Miranda, Kenneth
The use of social networking sites (SNSs), online learning tools (OLTs) amd learning management systems (LMSs) such as the University Virtual Learning Environment (UVLe) has been established in a number of universities in order to improve communication between students and faculty members without the confines of the traditional classroom.As there are no existing studies so far, this study was intended to identify the websites used by the UP College of Pharmacy (UPCP) students for their personal use and their frequency of use, the sites used for their respective courses, the perceptions of students on the use of SNSs, OLTs, and UVLe to facilitate learning and to describe the challenges encountered on the use of SNSs as means of filing sharing and information dissemination by educators. A survey was conducted on 215 students and 24 faculty members of the UPCP. Results showed that the most commonly used SNS and OLT were Facebook and Dropbox. Five percent of the faculty members required the use of UVLe in their academic courses. Decreased attention span and issues on privacy were the most widely encountered challenges by students and faculty members, respectively. Students and faculty perceive SNSs and OLTs as useful, easy to use, and are willing to adopt the two services as learning platforms. UVLe has mixed responses on its usefulness, ease of use, and its adoption as a learning platform. While UVLe is least commonly used by faculty and students, it overcomes the challenges encountered in SNSs and OLTs and may be recommended for use as the primary online learning management system in the College. Adequate training however must be provided to equip faculty and students on the functionality of this system
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, 2015.
Keywords: Online social networks